Wildlife Population Welfare as Coherence Between Adapted Capacities and Environmental Realities: A Case Study of Threatened Lamprey on Vancouver Island - Stephen, Craig; Wade, Joy (Frontiers in Veterinary Science, 2018)
Wildlife conservation lacks a well-accepted ethical foundation for population welfare. In this paper we propose a definition of wildlife population welfare and use a case study to suggest its value for species recovery planning. We define wildlife population welfare as coherence between the species’ adapted capacities and the realities of its current environment. We present a case study of the Cowichan Lake lamprey (Entosphenus macrostomus), a parasitic fish species endemic to three connected lakes in British Columbia, Canada. Individual-level welfare concerns were insufficient to inspire actions to protect this threatened species. The key threats to Cowichan Lake lamprey can be linked to anthropogenic changes and global threats such as climate change. Due to prevailing uncertainties and the inability to eliminate critical threats, the species recovery plan was focussed on securing critical environmental and social assets to meet evolved adaptations of lamprey while considering the needs of other species, including people. This assets focussed approach was well suited to developing consensus for action to enable a harm reduction perspective that recognizes that many of the threats cannot be eliminated but actions could be taken to enable the population to succeed by protecting critical environmental resources. This was consistent with our population welfare perspective which focusses on assets rather then deficits to help identify shared priorities for species recovery, conservation obligations and social expectations.